DNA flexibility studied by covalent closure of short fragments into circles. - Shore, D (1981)
The ring closure probability, or j factor, has been measured for DNA restriction fragments of defined sequence bearing EcoRI cohesive ends and ranging in size from 126 to 4361 base pairs (bp). The j factor is defined as the ratio of the equilibrium constants for cyclization and for bimolecular association via the cohesive ends. The end-joining reactions are fast compared to covalent closure of the cohesive ends by T4 DNA ligase. The rate of ligase closure is shown to be proportional to the equilibrium fraction of DNA molecules with joined cohesive ends, both in cyclization and in bimolecular association reactions. The j factor changes by less than 10-fold between 242 and 4361 bp, whereas it decreases by more than 100-fold between 242 and 126 bp as the DNA reaches the size range of the persistence length (150 bp). As regards ring closure, short DNA fragments are surprisingly flexible. These data are in good agreement with predictions by others for the ring closure probability of a wormlike chain.